Pengaruh Penjualan Dan Pembelian Terhadap Laporan Keuangan Pabrik Roti Aroma Jaya Padang - Oktaviani, Nichy (Jurnal Ekonomika Dan Bisnis (JEBS), 2021)
This study is about the effect of sales and purchases on the financial statements of the Aroma Jaya Padang Bread Factory with a ftable value that can be determined by looking at table F based on the df value of 27 and the significant value used is 0.05. So the value of ftable in this study is 3.37. And the results of the SPSS calculation show the value of fcount = 65.634 with a significance level of 0.000. Where the fcount > ftable and the significance value < 0.05. So, it can be concluded that the variables of sales and purchases simultaneously) have a significant influence on the financial statements. R Square value is 0.829 (82.9%). This means that all independent variables, namely sales and purchases, have a joint contribution of 82.9% to the dependent variable (Y), namely the financial statements, while the remaining 17.1% is explained by other factors outside of this study. the greater the number of R square, the stronger the influence of the two variables. Based on the research above, it can be suggested that the company increase profits by increasing sales and earning profits and it is recommended that financial statements be prepared in accordance with PSAK standards and can be considered for the Bank and other investors.'